Право на свободу вероисповедания сквозь призму постсекулярной парадигмы либеральной политической философии - Зелинская, Наталья Анатольевна; Зелинська, Наталя Анатоліївна; Zelinskaja, Natal'ja (My University, 2013)
The current issues of protection of the right to the freedom of religion in the context of post-secular paradigm of liberal political philosophy are approached in the article. The author studies the evolution of the European Court of Human Rights practice in this field. Particular attention is paid to the decisions in the cases Lautsi and others v. Italy and Eweida and others v. the United Kingdom.
Зелинская Н. А. Право на свободу вероисповедания сквозь призму постсекулярной парадигмы либеральной политической философии / Н. А. Зелинская // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 142-158.
Keywords: постсекуляризм; радикальный секуляризм; Европейский суд по правам человека; право на свободу мысли; совести и религии; религиозная идентичность; радикальний секуляризм; Європейський суд з прав людини; право на свободу думки; совісті і релігії; релігійна ідентичність; post-secularism; radical secularism; the European Court of Human Rights; the right to freedom of thought; conscience and religion; religious identity